The prevalence and risk factors of musculoskeletal disorders among subcontracted hospital cleaners in Thailand - Thanaphum Laithaisong (2022)
Purpose: This research aimed to explore the prevalence of musculoskeletal disorders (MSDs) and related factors among subcontracted cleaners in a teaching hospital in Thailand. Design/methodology/approach: A cross-sectional study was conducted of 393 subcontracted cleaners in a teaching hospital, from May to June 2020. Face-to-face interviews were carried out using a standard questionnaire, consisting of four parts: (1) participant characteristics, (2) stress test, (3) work characteristics and (4) standardized Nordic questionnaire, Thai version, for MSDs outcome. Multiple logistic regression analyses were performed to determine the association between MSDs and related factors. Findings: The prevalence of MSDs was 81.9%, involving mostly the lower back (57.7%), followed by the shoulder (52.6%). Factors significantly associated with MSDs were as follows: male gender (OR = 3.06, 95% CI [1.19, 7.87]), severe stress (OR = 2.72, 95% CI [1.13, 6.54]), history of injuries (OR = 4.37, 95% CI [1.27, 15.11]), mopping posture (OR = 2.81, 95% CI [1.43, 5.50]) and task duration (OR = 1.90, 95% CI [1.01, 3.57] for 2–4 h and OR = 3.39, 95% CI [1.17, 9.86] for more than 4 h). Sick leave due to MSDs was associated with history of injuries, Thai nationality and having another part-time job. Originality/value: The study findings about MSDs in terms of prevalence and related factors contributed to limited pool of the knowledge among subcontracted hospital cleaners in Thailand and middle-income country settings. With growing popularity in outsourcing cleaning services among hospitals in these countries, the study findings could raise a concern and inform policymakers and hospital administrators the importance of the magnitude and risk factors for MSDs necessitating design of preventive strategies.